Palladium(0) Nanoparticles Immobilized onto Silica/Starch Composite: Sustainable Catalyst for Hydrogenations and Suzuki Coupling - Ravinderpal Kour Sodhi; Satya Paul (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
The present paper aims to give insight into the art in the field of the synthesis, characterization and applications of Pd(0) nanoparticles immobilized onto silica/starch composite (SS-PdNPs) for hydrogenations and Suzuki coupling. Metal(0) nanoparticles immobilized onto silica/starch composite [SS-MNPs] were prepared from different metal acetylacetonate complexes [Co(acac)2], [Cu(acac)2], [Pd(acac)2], [Ru(acac)3], [Mn(acac)3], [Co(acac)3] by immobilizing onto silica/starch composite, followed by reduction with NaBH4. Excellent yield of the products, reusability and the facile work-up makes SS-PdNPs a unique catalyst for the reduction of nitroarenes/carbonyl compounds, a,b unsaturated carbonyl compounds and Suzuki coupling under environmentally benign reaction conditions. All the catalysts were characterized by Fourier Transform Infra Red (FTIR), Atomic Absorption Spectroscopy (AAS) analyses, while the most active catalyst [SS-PdNPs] was further characterized by Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM).